Ancient schwannoma of the tongue: a case-report and literature review - Soncini, Arianna; Lazio, Maria Silvia; Salsi, Daria; Celaschi, Chiara; Cuda, Domenico (Acta Biomedica Atenei Parmensis, 2024)
Schwannomas are benign tumors arising from Schwann cells of the nerve. Although they commonly appear in the soft tissues of the head and neck (25%), the intraoral origin (1%) and the ancient histological subtypes represent the rarest variant. Specific diagnosis is difficult and often delayed. Radiological examination can be helpful, but complete excision remains the treatment of choice to obtain histological information and reduce the risk of recurrence. We report a rare case of intramural schwannoma of the tongue in a 80-year-old male patient, excised completely via a transoral approach. Histophatological examination and immunohistochemistry confirmed diagnosis and the patient had no postoperative complications. We performed a literature review with a PubMed search about schwannomas of the mobile tongue about the last 30 years. We found 585 articles, of which 54 met the inclusion criteria with a total of 90 cases of schwannoma of the tongue. We finally described the most relevant features of these tumors and their management.